Left Ventricular Adaptations in Herding Dogs - Costa Martins, Raimy; da Exaltação Pascon, João Paulo; Guzmán Béltran, Karen; de Arruda Mistieri, Maria Ligia (Acta Scientiae Veterinariae, 2019)
Background: Athlete’s heart syndrome comprises a set of functional and anatomic cardiac changes secondary to intense and prolonged physical exercise in humans and animals. The heart adapts to the type of activity performed, and Doppler echocardiography is the best tool for identifying these changes. Speckle tracking echocardiography (STE) has provided new data on cardiovascular adaptations secondary to physical exercise in humans, information that conventional echocardiography cannot provide. Although physical activity and work in dogs are well documented, there are few studies on cardiovascular adaptations secondary to exercise in dogs, and no studies to date evaluated these adaptations using STE. Materials, Methods &Results:A total of 31 dogs of the Border Collie and OvelheiroGaúchoBrasileiro breeds were divided into two groups: a herding group (HG, n = 15), which performed herding activity five to six times a week for at least 4 months, and a sedentary group (SG, n = 16), with no history of physical activity in the past twelve months. All dogs were previously subjected to electrocardiography and blood pressure measurement. After that, the animals underwent echocardiographic examination at rest at a single time point. The data were analyzed by two-way multivariate analysis of variance (ANOVA) at a level of significance of 5% (P < 0.05) and a trend at 90% (P < 0.1). The dogs of the HG had higher values for left-ventricular end-systolic diameter (LVESD) and systolic volume (SV), and lower values for left-ventricular myocardial performance index (Tei index) and systolic septal movement. STE results indicated that the HG presented lower values for strain and strain rate in some myocardial segments in the radial, circumferential, longitudinal, and transverse directions. Discussion:The increase in LVESD is justified by the increase in preload (volume) required to meet the increased oxygen demand, whereas SV is directly related to the Frank-Starling mechanism. The lower Tei index in the HG indicates better systolic-diastolic performance, explained by a shorter isovolumetric relaxation time and isovolumetric contraction time and by an increase in left ventricular (LV) ejection time. Similar results were not observed in LV systolic wall motion. Therefore, we believe that the most likely explanation is a higher systolic efficiency, associated with lower energy demand at rest. According to STE criteria, the lower strain and strain rate in the HG in some myocardial segments in all directions suggest less need for myocardial deformation and lower deformation velocity in order to maintain systolic function. In conclusion, conventional echocardiography and STE were complementary and fundamental to understand cardiovascular adaptations in herding dogs.